Influence of Preoperative Oropharyngeal Microflora on the Occurrence of Postoperative Pneumonia and Survival in Patients Undergoing Esophagectomy for Esophageal Cancer. Issue 6 (December 2020) - Yuda, Masami; Yamashita, Kotaro; Okamura, Akihiko; Hayami, Masaru; Fukudome, Ian; Toihata, Tasuku; Imamura, Yu; Mine, Shinji; Ishizuka, Naoki; Watanabe, Masayuki
Abstract : Objective: The aim of this study was to clarify the correlation between oropharyngeal microflora and postoperative complications as well as long-term survival after esophagectomy. Background: Although the oral cavity is known to be a potential reservoir for pathogens, the influence of abnormal oropharyngeal microflora on the outcomes of patients undergoing esophagectomy remains unknown. Methods: This study included 675 patients who underwent esophagectomy between 2007 and 2014. Saliva samples from the oropharynx were collected 2 days before the operation. There were 442 patients with indigenous flora (Ind group) and 233 with allopatric flora. Among the patients with allopatric flora, 140 had antibiotic-sensitive microbes only (Allo-S group) while 93 had different types of antibiotic-resistant microbes (Allo-R group). We investigated the correlation between the types of oropharyngeal microflora and the incidence of postoperative complications as well as long-term outcomes. Results: Sixteen microbes could be cultivated from the saliva samples. The incidence of postoperative pneumonia in the Allo-S and Allo-R groups was significantly higher than in the Ind group ( P < 0.001). In addition, acute respiratory distress syndrome was more often observed in the Allo-R group than in the other groups ( P = 0.002). A significantly higher rate of antibiotic use and longer hospital stays were observed in the Allo-R group compared with the Ind group. Multivariate logistic regression analysis revealed that the presence of allopatric antibiotic-resistant microbes in the oropharynx was an independent risk factor for postoperative pneumonia (odds ratio, 3.93; 95% confidence interval, 2.41–6.42). The overall survival was significantly poorer in the Allo-R group than in the other groups. Conclusions: Preoperative oropharyngeal culture is a simple and low-cost method that can predict both the occurrence of postoperative pneumonia and poor prognosis after esophagectomy. Abstract : Supplemental Digital Content is available in the text